2016
DOI: 10.3111/13696998.2015.1131704
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of medical costs and healthcare resource utilization of post-menopausal women with HR+/HER2− metastatic breast cancer receiving everolimus-based therapy or chemotherapy: a retrospective claims database analysis

Abstract: This retrospective claims database analysis of commercially-insured patients with HR+/HER2- mBC in the US showed that everolimus was associated with substantial all-cause, BC-related, and AE-related medical cost savings and less utilization of healthcare resources relative to chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Six studies (29%) reported the period of observation as ‘during treatment’ [ 28 , 29 , 34 , 39 , 40 , 44 ]. Three studies (14%) made no statement about the period of observation [ 31 , 32 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies (29%) reported the period of observation as ‘during treatment’ [ 28 , 29 , 34 , 39 , 40 , 44 ]. Three studies (14%) made no statement about the period of observation [ 31 , 32 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies (30%) reported that ED presentations recorded were ‘all-cause’ and included all ED presentations made by cancer patients that fell within the period of observation [ 32 , 33 , 38 , 40 , 41 , 44 ]. Five studies (25%) recorded ED presentations that were defined as specifically relating to treatment; one study (5%) [ 37 ] used a previously developed algorithm used to identify chemotherapy related adverse events in breast cancer patients [ 10 ], and two studies reported on a priori defined common adverse events related to SACT [ 28 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations